Integrative taxonomy of Asiopodabrus fragiliformis (Kang and Kim, 2000) (Coleoptera: Cantharidae) and its related species - Kang, Tae Hwa; Han, Tae Man; Okushima, Yûichi; Park, Hae Chul (Zootaxa, 2012)
Both the color patterns of the body and the structures of the male genitalia are important characters used in speciesidentification of traditional taxonomy. However, these characters are often limiting when identifying females of somespecies. In this study, we attempted to evaluate the species reality of Asiopodabrus fragiliformis which often has difficultyin being identified due to individual variation in color pattern and lack of female information. Using DNA barcoding, A.fragiliformis was represented as having three clades strongly supported by a high bootstrap value (>99%) and with over3% branch lengths having a 2.9–3.4% barcoding gap. Morphological reexamination based on the result of DNAbarcoding, demonstrated three clades: A. fragiliformis, A. kurvatovi, and A. koryeoensis n. sp., respectively, that wereclarified based on subtle difference in both male and female morphological characters. This study explicitly showed thatDNA barcoding may clearly and rapidly decide the species delineation for morpho-species in certain cases when the identification of female specimens is not clear using traditional methods.